Comparative Computational Study of Frequency Shifts and Infrared Intensity Changes in Model Binary Complexes with Red- and Blue-Shifting Hydrogen Bonds - Sean A. C. McDowell (Molecules)
A computational study of X-H···Y binary hydrogen-bonded complexes was undertaken to examine the red- and blue-shifting behavior of three model X-H proton donors interacting with a series of Lewis bases: Y = NH3, NCLi, NCH, NCF, C2H2, BF, CO, N2 and Ne. Two of these proton donors, FArH and F3CH, have blue-shifting tendencies, while the third, FH, has red-shifting tendencies. A perturbation theory model for frequency shifts that was derived many years ago was employed to partition the predicted frequency shift into the sum of two components, one dependent on the second derivative of the interaction energy with respect to X-H displacement and the other dependent on the X-H bond length change in the binary complex. The predicted shifts were found to be in good agreement with standard ab initio computations, but they were obtained at much lower computational cost. The change in the infrared intensity of the X-H stretching frequency, expressed as a ratio of complex to monomer intensities, was also investigated, along with its relation to the X-H permanent dipole moment derivative and total induced dipole moment derivative with respect to X-H displacement, and used to rationalize the observed infrared intensity changes in the red- and blue-shifted X-H···Y complexes.